Pengaruh Pembatasan Pakan Terhadap Bobot Akhir, FCR dan Income Over Feed Cost pada Pemeliharaan Ayam Broiler dengan Kandang Closed House - Maulana, Muhammad Irfan; Herlina, Linda; Firman, Achmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Feed costs present a challenge in the process of raising broiler chickens in closed house systems, as feed expenses account for 70% of the total production costs. Therefore, strategies need to be developed to minimize feed costs while maintaining chicken performance. One of the strategies that can be applied is restricted feeding. In this study, the effect of feed restriction on final weight, FCR, and Income Over Feed Cost (IOFC) was analyzed. The study was conducted by observing and recording data from broiler farming with ad libitum feeding and restricted feeding treatments, each over 14 periods. The observed parameters were final weight, FCR, and IOFC, and the data were processed using T-tests in SPSS. The results showed that feed restriction treatment did not have a significant effect on final weight, FCR, or Income Over Feed Cost. However, when viewed from the data averages, feed restriction treatment resulted in lower body weight, lower FCR, and higher IOFC.